2007
DOI: 10.1002/bem.20375
|View full text |Cite
|
Sign up to set email alerts
|

Perception of the electromagnetic field emitted by a mobile phone

Abstract: Electromagnetic sensibility refers to the ability to perceive the electromagnetic field (EMF) without necessarily developing health symptoms attributed to EMF exposure. A large sample of young healthy adults (n = 84) performed two forced-choice tasks on the perception of the GSM mobile phone EMF (902 MHz pulsed at 217 Hz), "Was the field on?" and "Did the field change?" (3 conditions x 100 trials for each task, n = 600 trials in total). A monetary prize was announced for good performance (correct response rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 14 publications
1
24
0
3
Order By: Relevance
“…Chance is, however, not a plausible explanation for the exceptional accurate on/off judgment of two participants in one trial because the p-values were below 10 À21 [29]. The probability of achieving such a performance by chance is as low as achieving six correct hits in a lottery (6 out of 49) three times in a row.…”
Section: Discussionmentioning
confidence: 93%
“…Chance is, however, not a plausible explanation for the exceptional accurate on/off judgment of two participants in one trial because the p-values were below 10 À21 [29]. The probability of achieving such a performance by chance is as low as achieving six correct hits in a lottery (6 out of 49) three times in a row.…”
Section: Discussionmentioning
confidence: 93%
“…Frick et al [2005] reported that their experiment using transcranial magnetic stimulation did not support the hypothesis that subjectively electrosensitive patients suffered from a physiological hypersensitivity to EMFs stimuli. Another study by Kwon et al [2008] also provided lack of evidence for the existence of electromagnetic perception to the Global System for Mobile Communications (GSM) mobile phone EMF. In a recent review, Röösli [2008] concluded that the available provocation studies do not indicate that people can perceive radio frequency (RF)-EMF or that symptoms are directly invoked by them.…”
Section: Introductionmentioning
confidence: 99%
“…The following studies reported various subjective symptoms: Aringer et al [1997], Koivisto et al [2001], Hietanen et al [2002], Hillert et al [2002], Wilen et al [2006], Eltiti et al [2007], Oftedal et al [2007], Röösli [2008]. A few EMF perception studies include: Mueller et al [2002], Leitgeb and Schröttner [2003], Rubin et al [2006], Kwon et al [2008].…”
Section: Introductionmentioning
confidence: 99%
“…Ponieważ ucho sąsiaduje ze źródłem PEM, którym jest telefon komórkowy, więk-szość badań ukierunkowywano na sprawdzenie oddziaływania PEM na układu słuchowy, w tym na słu-chowe potencjały wywołane -w trakcie lub po ekspozycji, a nawet po ekspozycji wielokrotnej. Nie zaobserwowano w tych badaniach żadnych skutków oddziały-wania PEM [37][38][39][40][41][42][43][44][45][46]. Również badania na zwierzętach nie wykazały takiego oddziaływania [47].…”
Section: Wpływ Pem Na Potencjały Wywołaneunclassified